ERM proteins support perinuclear actin rim formation - Hadad, Yuval; Fracchia, Andrea; Babele, Dagmawit; Ben Shushan, Amit; Gerlitz, Gabi (Frontiers in Cell and Developmental Biology, 2026)
The interaction of actin filaments with the nuclear envelope is essential for diverse cellular processes, including cell migration, nuclear positioning, and transcriptional control. The main studied mechanism that links F-actin to the nucleus is the Linker of Nucleoskeleton and Cytoskeleton (LINC) complex. Recently, the formation of a perinuclear actin rim has been identified in various cell types in response to external force or migration signals. This rim depends on the activation of the actin nucleator Inverted formin 2 (INF2) by calcium influx. However, it is unclear how the rim is coupled to the nuclear envelope. Here, we show that the nuclear membrane protein Emerin, which has an actin-binding domain, is not required for the perinuclear actin rim formation. Interestingly, we found that the Ezrin-Radixin-Moesin (ERM) proteins, known to link actin filaments to the cell membrane, are also localized to the nuclear envelope in melanoma cells. Knockdown of ERM proteins led to a reduction in the rim levels, while overexpression of ERM proteins increased the perinuclear actin rim levels. Overexpression of Ezrin also improved the rim formation in HeLa cells upon addition of a calcium ionophore. Thus, the ERM proteins appear to participate in a mechanism that links actin filaments to the nuclear envelope.